Hubungan Status Kesehatan dan Status Gizi Anak Terhadap Perkembangan Motorik Kasar Anak Usia Toddler di Pilangsari Puskesmas Kedawung Kabupaten Cirebon - Supriatin, Titin (Cerdika: Jurnal Ilmiah Indonesia, 2022)
When compared with Western countries, the child's motor development milestones in Indonesia are low. In America, children started running at the age of 11.4 to 12.4 bulan11, and children in Europe between 12.4 to 13.6 bulan12. While in Indonesia, the studied sample was 14.02 months. To determine the relationship of health status and nutritional status of the child's gross motor development in children aged toddler in Pilangsari Kedawung District Health Center in Cirebon. This study is correlative analytic. The approach used in this study was cross-sectional. The population in this study were all aged children at the health center toddler Pilangsari Kedawung Cirebon, as many as 58 people. 58 samples, data analysis using Spearman's rho. Most research results toddler memiliki childhood health status is good enough that as many as 28 people (48.3%), majority of children aged toddler had good nutritional status, namely a total of 39 children (67.2%), Most children have a developmental age toddler Gross motor in the normal category as many as 38 people (65.5%). There is a relationship of health status on the development of gross motor skills in children aged toddler Pilangsari Kedawung Cirebon District Health Center.